EU Bank recapitalisation and the bail-in option: an analysis of the effects of mandatory bail-in on creditors’ property rights - Maguze, Tracy Chiyedza (2021)
As of 1 January 2016, all members of the European Union (EU) are required to have bail-in provisions as part of their national bank resolution and recapitalisation legislation. The bail-in of bank creditors’ claims in order to recapitalise the bank is not a new phenomenon, it was utilised in Cyprus in 2013 and has since been used in a series of rescue operations launched for struggling banks in Austria, Slovenia, Greece, Italy, Hungary, Denmark, and Portugal. One of the most obvious concerns with the bail-in tool is that it deprives bank creditors of their property, namely a right to claim repayment of a debt obligation. The object of this paper is to determine if bail-in rules actually interfere with the right to property of bank creditors and whether such interference is unjustified. The paper concludes that, firstly, bail-in amounts to an interference with peaceful enjoyment of property and, secondly, such interference cannot be justified because bail-in rules fall short of the legality and legitimacy requirements which must be met when the State interferes with the right to property. Bail-in rules infringe bank creditors’ right to property and, as such, present a legal risk to resolution authorities in Member States.